2020
DOI: 10.4028/www.scientific.net/jnanor.62.59
|View full text |Cite
|
Sign up to set email alerts
|

The Differentially Effect of Some Antilipid Drugs on Activity of the Novel Synthesized Paraoxonase (PON1)-Inorganic Hybrid Nanoflowers

Abstract: In the present study, the hybrid nanoflower PON1-Ca2+ (hNF-PON1) structure was synthesized and characterized and some antilipid drugs effects were investigated on hybrid paraoxonase (PON1) activity. Firstly, the hPON1 enzyme was purified 304.5 fold with 76.4% yield from human serum using the triple phase separation technique (TPP). Then, the hNF-PON1 was prepared in a one-step procedure using biomimetic mineralization. The catalytic activity of the hybrid enzyme with an 88.49% binding rate increased by 26.40%.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
0
0
Order By: Relevance
“…Biomolecules possess charged amino acid groups in their inner structure which enable them to diffuse inorganic salts and produce desired NPs in a simple and environment friendly manner. After the accidental discovery of organic-inorganic hybrid nanoflowers, researchers have been devoted to exploring different synthetic strategies for the preparation of protein-inorganic hybrid nanoflowers due to their promising applications [86][87][88]. In this connection, Zhang et al [71] reported a facile, rapid and low cost method to fabricate enzyme immobilized, lipase/Zn3(PO4)2 hybrid nanoflowers to study their catalytic activity.…”
Section: Biological Methodsmentioning
confidence: 99%
“…Biomolecules possess charged amino acid groups in their inner structure which enable them to diffuse inorganic salts and produce desired NPs in a simple and environment friendly manner. After the accidental discovery of organic-inorganic hybrid nanoflowers, researchers have been devoted to exploring different synthetic strategies for the preparation of protein-inorganic hybrid nanoflowers due to their promising applications [86][87][88]. In this connection, Zhang et al [71] reported a facile, rapid and low cost method to fabricate enzyme immobilized, lipase/Zn3(PO4)2 hybrid nanoflowers to study their catalytic activity.…”
Section: Biological Methodsmentioning
confidence: 99%